Customer Satisfaction Perspective in Public Sector Banks: Post Privatisation Scenario - Kaur, Amrinder (Gyan Management Journal, 2010)
lndian banking sector has undergone gone metamorphous change in the last couple of decades after onset of reforms in the financial sector. Public sector banks, which are the back bone of Indian financial system and has created huge infrastructure over the years, were marred by poor customer service and financial viability. However, the privatisation in the banking sector acted as catalyst and as such these banks have undergone comprehensive reorganization of their business model. The present research paper endeavors to appraise the customer satisfaction scenario in the Public Sector Banks in relation to For_eign Banks. The comparative study of the satisfaction level of the customers of Public Sector Banks and Foreign Banks reflects two view points. The study brings out that sizable number of customers is satisfied with the Public Sector Banks largely because of their traditional approach and mind set towards banking and the personal attention provided by them.